PENGARUH PEMBERIAN BERBAGAI KONSENTRASI GIBBERELLIC ACID DAN JENIS VARIETAS TERHADAP PERTUMBUHAN DAN HASIL TANAMAN CABAI RAWIT (Capsicum frutescens L.) - Imas Rohmawati; Dewi Hastuti; Purwati . (Jurnal Agroekoteknologi, 2018)
The research was aimed to know the effect of the gibberellic acid concentrations and types of varieties on the growth and yield of cayenne pepper (Capsicum frutescens L.). Research was conducted from November 2017 until April 2018 in Ciruas Village, Ciruas District, Serang Regency, Banten Province. This research used Randomized Completely Block Design with two factors and three replications. The firs factor was concentration of gibberellic acid (GA3)  wich consisted five levels namely G0=0 ppm, G1=10 ppm, G2=20 ppm, G3=30 ppm, G4-40 ppm. The second factors was  types of varieties wich consisted two levels namely V1=Hybrids (Pelita), V2=Non Hybrids (Tripang). The parameters observed were plant height, number of leaves, Flowering age, number of flowers, percentage of fall flowers, age of fruit harvest, number of fruits and  the weight of fruit. The result showed that the concentration of GA3  has no significant effect on all parameters. Type of varieties gave significant effect on plant height, number of leaves, flowering age, number of flowers and age of fruit harvest. Type of varieties V1 (hybrids) gave the average on the number of leaves 6  weeks after planted (92,07 sheet), flowering age (42,13 day after planting), and age of fruit harvest (90,26 day after planting). There was no interaction between concentration of GA3 and types of varieties on all parameters. Keyword: Cayenne pepper, Concentration of GA3, Types of varieties